2005
DOI: 10.1055/s-2005-872844
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Heterogeneity in Two Unrelated Danon Patients Associated with the SameLAMP‐2Gene Mutation

Abstract: Danon disease, an X-linked cardioskeletal myopathy caused by primary deficiency of lysosome-associated membrane protein-2 (LAMP-2), is clinically characterized by cardiomyopathy, myopathy, and variable mental retardation. The pathological hallmark of the disease is the absence of LAMP-2 immunohistochemical staining in muscle. The LAMP-2 gene mutations reported thus far are generally private mutations. We describe two cases of Danon disease with different clinical presentation, in whom we identified the same ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0
5

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 8 publications
3
19
0
5
Order By: Relevance
“…2C). This pattern was similar to what was observed for other lysosomal markers, such as CD63 (Bertini et al, 2005;Yang et al, 2005) and cathepsin D (data not shown).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…2C). This pattern was similar to what was observed for other lysosomal markers, such as CD63 (Bertini et al, 2005;Yang et al, 2005) and cathepsin D (data not shown).…”
Section: Resultssupporting
confidence: 89%
“…Use of the H4B4 mouse monoclonal Ab (Iowa Hybridoma Bank) prevails (Supplementary Table 1), although information about its antigenic specificity is lacking, as previously noted by Bertini et al (2005). In agreement with the report by Nishino et al (2000) on the LAMP2B isoform mutation and the results of our testing, we may assume that this Ab is not specific for a particular LAMP2 isoform because it detected all three LAMP2 splicing variants that were separately expressed in the LAMP2-deficient fibroblasts from patient III/3 (data not shown).…”
Section: Gross Pathology Histopathology and Immunohistochemistrymentioning
confidence: 98%
“…The earliest reported onset of symptoms was at age 4 months in a male patient who presented with hypotonia and cardiac failure. 19 Further diagnostic examination revealed severe obstructive hypertrophic cardiomyopathy on echocardiography and marked vacuolar myopathy on muscle biopsy. 19 Females generally present later in childhood or early adulthood and have a more protracted course.…”
Section: Clinical and Diagnostic Manifestationsmentioning
confidence: 99%
“…While the inheritance pattern is X-linked dominant, de novo mutations have also been reported. 6, 7 The exon-skipping mutation c.928G>A (skips exon 7) is the most frequent mutation reported in the LAMP2 gene, 19 although mutations may be present in every exon. Most mutations are nonsense or frameshift mutations predicted to truncate the LAMP2 protein, resulting in absence of the transmembrane and cytoplasmic domains and likely disabling its function as a lysosomal membrane protein.…”
Section: Lamp2 Mutationsmentioning
confidence: 99%
“…AVSFs should be located near the peripheral sarcolemma if they are sarcolemma-derived but, because they are instead found scattered throughout the cytoplasm, it is thought that these AVSFs are generated through a poorly understood de novo biogenesis process (Endo et al, 2015). Disease-associated skeletal muscle vacuoles have also been reported to accumulate glycogen (Bertini et al, 2005;He et al, 2014;Yang and Vatta, 2007), degenerating mitochondria (Yang and Vatta, 2007), lipids (Bertini et al, 2005) and basophilic granules (implicating buildup of lysosomal organelles in the myofibers) (He et al, 2014;Sugie et al, 2005;Endo et al, 2015;Dougu et al, 2009), and to express increased levels of LC3 and ubiquitin (Endo et al, 2015).…”
Section: +mentioning
confidence: 99%